White night a novel of the Dresden files - Butcher, Jim (New York, NY : Roc, 2008)
Assigned to investigate the deaths of several magic practitioners, all of whom lacked the ability to become full-fledged wizards, professional Chicago wizard Harry Dresden is shocked when the evidence points to his half-brother Thomas as the killer.
Includes a preview of Burning alive by Shannon K. Butcher.
Keywords: Dresden, Harry (Fictitious character); Wizards -- Illinois -- Chicago; Private investigators -- Illinois -- Chicago; Magicians -- Crimes against; Brothers; Chicago (Ill.); Fantasy fiction